Centroid Estimation Method Based on the Statically Equivalent Serial Chain of the Human-exoskeleton-load Coupling System - Deng Rong; Liu Fang; Huang Taotao; Song Zepeng; Xu Peisen; Huang Wenjian (Jixie chuandong)
The existing centroid estimation methods only study the changes of the centroid of exoskeletons, and ignore the coupling between the human body and exoskeletons. In order to study the change of the centroid in the human-exoskeleton-load coupling system, a centroid estimation method based on the statically equivalent serial chain was proposed. Firstly, a human-exoskeleton-load coupling system model was established, and the kinematic parameters required for the model were acquired by the human motion characteristics experiment. Secondly, the experimental process was simulated in the OpenSim simulation environment, and the changes of the center of mass of the human-exoskeleton-load coupling system under different loading conditions were obtained. Finally, the feasibility of the centroid model was proved through the theoretical calculation and the simulation, which provides a theoretical basis for the research of exoskeletons in the human-machine carrying.